2010
DOI: 10.1021/jm901621h
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Insulin Secretagogue Based on a Dinucleoside Polyphosphate Scaffold

Abstract: Dinucleoside polyphosphates exert their physiological effects via P2 receptors (P2Rs). They are attractive drug candidates, as they offer better stability and specificity compared to nucleotides, the most common P2 receptor ligands. The activation of pancreatic P2Y receptors by nucleotides increases insulin secretion. Therefore, in the current study, dinucleoside polyphosphate analogues (di-(2-MeS)-adenosine-5′,5″-P1,P4,α,β-methylene-tetraphosphate), 8, (di-(2-MeS)-adenosine-5′,5″-P1,P4,β,γ-methylene-tetraphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…P2 agonists have already been suggested as having a beneficial effect in models of melanoma, in which the P2Y 1 receptor is highly expressed [10]. Other potential therapeutic applications under consideration for P2Y 1 receptor ligands include: selective agonists as antidiabetic agents [32] or selective antagonists as antithrombotic agents [33]. P2Y 1 agonists that are dinucleotides with enhanced in vivo stability have been reported [32].…”
Section: Discussionmentioning
confidence: 99%
“…P2 agonists have already been suggested as having a beneficial effect in models of melanoma, in which the P2Y 1 receptor is highly expressed [10]. Other potential therapeutic applications under consideration for P2Y 1 receptor ligands include: selective agonists as antidiabetic agents [32] or selective antagonists as antithrombotic agents [33]. P2Y 1 agonists that are dinucleotides with enhanced in vivo stability have been reported [32].…”
Section: Discussionmentioning
confidence: 99%
“…Blood serum contains such enzymes and, therefore, provides a good model system for estimation of the in vivo stability of nucleotide analogues. 42,43 Here, we evaluated the stability of the most promising analogue identified here, 7A, in human blood serum as compared to 2, and 6A.…”
Section: Resistance Of 7 A/b To Hydrolysis By Ecto-nucleotidasesmentioning
confidence: 99%
“…It has been suggested that 2-methylthio ATP-a-b, A isomer, a potent and tissue-selective P2Y 1 receptor agonist with high efficacy for glucose-dependent insulin secretion, may be a drug candidate for type 2 diabetes (Farret et al 2006). Dinucleoside polyphosphate analogues, which offer better stability compared to nucleotide, acting through P2Y 1 receptors have been developed as insulin secretagogues and it was suggested that they may prove to be an effective and safe treatment for type 2 diabetes (Eliahu et al 2010).…”
Section: Diabetes and Pancreasmentioning
confidence: 99%